Anticoagulant-induced Pseudothrombocytopenia and Pseudoleucocytosis - Schrezenmeier, Hubert; Müller, Hilke; Gunsilius, Eberhard; Heimpel, Hermann; Seifried, Erhard (Thrombosis and Haemostasis, 1995)
Pseudothrombocytopenia (PTP) is the phenomenon of falsely low platelet counts due to in vitro platelet clumping in the presence of platelet autoantibodies and anticoagulants. We assessed anticoagulant- dependence, time course of platelet counts and impact of different counter devices on the phenomenon. Blood of 10 persons with previously recognized pronounced EDTA-dependent PTP was collected into 7 different anticoagulants and counted after different intervals in parallel in a Coulter T540 and a Coulter STKS counter and by phase contrast microscopy. With the Coulter T540 model PTP was most pronounced in blood samples anticoagulated with EDTA, Na-oxalate or Na-citrate. In the STKS counter EDTA, heparin and oxalate presented as the worst anticoagulants. The time course of platelet counts was significantly different between the two counters. Our results demonstrate that PTP is not restricted to EDTA, but is also present with other anticoagulants. In contrast, pseudoleucocytosis was observed only in EDTA-anticoagulated blood in the Coulter T540 device.We investigated the expression of platelet integrins and activation antigens on platelets of persons with anticoagulant-dependent PTP and in healthy controls without PTP. In the presence of EDTA the expression of GpIIb/IIIa was significantly reduced in the PTP subjects compared to control. Activation antigens CD62, CD63 and thrombospondin-antigen were upregulated in the presence of EDTA. These alterations in the expression of platelet antigens could also be induced on platelets of normal donors by incubation with sera of PTP subjects and EDTA. The downregulation of GP IIb/IIIa in EDTA-blood of PTP subjects supports the hypothesis that the GPIIb/IIIa complex might be the binding site for the anti-platelet antibodies present in the sera of PTP subjects. Our results suggest that the binding of the autoantibodies causes platelet activation similar to other platelet-activating stimuli leading to subsequent platelet agglutination.